SIVATHERIUM (ARTIODACTYLA, RUMINANTIA, GIRAFFIDAE) FROM THE UPPER SIWALIKS, PAKISTAN - A. A. Khan; M. A. Khan; M. Iqbal; M. Akhtar; M. Sarwar (Journal of Animal and Plant Sciences, 2011)
A complete lower molar series ofgiraffid remains from the Pleistocene locality of the village Sardhok (Gujrat, Punjab, Pakistan) has been identified as belonging to Sivatherium sp. The comparison of the material was made with several Siwalik representatives of the giraffids. The giraffid Sivatherium is a gigantic giraffid found in the early Pleistocene sediments of the Upper Siwaliks. The village Sardhok locality has yielded one of the best collections of Giraffidae from the early Pleistocene of the Siwaliks. The locality belongs to the Pinjor Formation of the Upper Siwaliks (2.6-0.6 Ma).
Keywords: Giraffids; Sivatherium; Upper Siwaliks; Pleistocene; Pinjor Formation